PEMBELAJARAN BAHASA ARAB: SEBAGAI SEBUAH SISTEM - Sokip, Sokip; Nuryani, Nuryani (Jurnal Bahasa Lingua Scientia, 2012)
To make a teaching and learning effective and efficient, it is needed a systematic management of classroom. The components supporting a good management are teaching objectives, students, teachers, methods, facilities, environment, and evaluation. Each component influences the success of learning. Yet, among those components, teacher is the most important since a teacher is so dynamic that he will be able to manage and drive the other components.